Psychology for Economists - Piet K. Keizer (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2010)
Orthodox economics focuses on the analysis of the way the economic force or motivation operates, thereby abstracting from the functioning of other primary forces or motivations, such as the social and the psychic motivation. By assuming perfect rationality psychic problems are ignored. This text discusses six approaches in psychology – cognitive, behaviourist, biological, psychodynamic, humanistic and social psychology - to find out what orthodox economics needs in order to extend its analysis with the more realistic idea of imperfect rationality. In this discussion the state of the art of behavioural economics in included.
Keywords: 330; orthodox economics; psychology; behavioural economics; imperfect rationality